Table of contents, editorial board, introduction from the editor, and other front matter - Hal R. Taylor (Journal of Applied Communications, 1982)
Editorial front matter and table of contents for vol.65, no.1, Jan-Mar (1982) of The ACE Quarterly, Official Journal of the Agricultural Communicators in Education